Criticism Towards Shaḥrūr's Concept of The Prophet's Sunnah - Fahmi Ali Syaifuddin Rizal (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2021)
This article deals with the concept of Sunnah proposed by Muḥammad Shaḥrūr and offers a criticism towards his tendency to the denial of the Prophet’s Sunnah (inkār al-Sunnah). Shaḥrūr rejects the Ḥadīth and Sunnah as the second source of Islamic law, by reformulating and redefining the concept of Ḥadīth and Sunnah. Shaḥrūr distinguished between Ḥadīth and Sunnah. According to him, the Ḥadīth is the Qur’ān itself, and the Sunnah has been the practical application (ijtihād) of the Prophet to implement what was revealed to him. Shaḥrūr’s rejection and denial of Ḥadīth and Sunnah are based on the argument that all Ḥadīths were filled with the story of Isrā’īliyyāt. The tendency towards inkār al-Sunnah represented by Shaḥrūr is not a completely new idea, since this position was also conceived by several previous figures. However, despite the fact that Shaḥrūr’s inkār al-Sunnah as argued on the basis of a new approach to Ḥadīth studies, this article reveals that Shaḥrūr’s understanding of, and his tendency to deny, Ḥadīths or Sunnah reflect his opposition against orthodox views on the Prophet’s Sunnah.